Splenic artery aneurysm.: 3 new cases. - Torres, Marcos; Vallverdú, Martín; Bentancur, Bernabé; Bianchi, Carlos; Silva, Guillermo (Cirugía del Uruguay, 1987)
3 new cases o! splenic artery aneurysms treated with good results are presentad. In one case that ruptured, the diagnosis was intraoperatory, in the others radiology and new imagenology techniques (CAT sean) were of value. Low speciflcity of symptomatology • is polnted out. Sorne considerations about clinical presentation and therapeutic are done.